Virtual reality based rehabilitation system for Parkinson and multiple sclerosis patients - Kihe, Maria Merve; Çatal, Çağatay; MURATLI, ÖMER CAN (IEEE, 345 E 47Th St, New York, Ny 10017 USA, 2017)
The aim of this study is to present a virtual reality based rehabilitation system for Parkinson and Multiple Sclerosis (MS) patients. In this study, physical rehabilitation software has been developed using Virtual Reality (VR) technology. The VR environment was used to find a unique solution to the problems of balance, tremor and movement coordination that MS and Parkinson patients suffer from. Virtual reality environment was designed and implemented using UNITY 3D game engine. The generated virtual environment was supported by Kinect, delivered to the virtual reality viewer of Google Cardboard with third party software, and this whole system provided the virtual reality environment. The interaction of the patients with the virtual environment helped these patients to tackle with their problems. The movements in the joint area of the patient were detected using the Microsoft Kinect human-machine interface. Kinect transferred user movements to the computer based on the serial communication. This prototype system will be deployed into a rehabilitation center in Turkey for in-depth analysis and experiments.
Keywords: Virtual Reality; Software Systems; Health Informatics; Biomedical Systems; Human-Computer Interface; Unity for Virtual Reality; Randomized Controlled-Trial; Postural Control; Fatigue; Disease; People; Disability